Rebooting Staff Performance Appraisal system (PA) at ADA University - Hasanova, Aydan (ADA University, 2020)
Assessments of the performance were the topic of much scientific study, scholarly literature, and practitioners' advice. While reviewing published works on the subject when strolling through a bookstore's aisles. And if there is an experienced manager in a traditional business organization, then undoubtedly that manager saw one new performance assessment program after another being implemented and retired. At ADA University as well, the same happened with the PA system, which began to be implemented first in 2012 and stopped in 2016. The system and the organization had challenges, problems, thus it had to stop. Despite there was a nice globally adjusted PA Manual, during the system implementation period there were some broken links to the real application. Unknown goals that were not aligned with strategic ones, directors setting simple KPIs, less automated system, and backup problems with the budget challenges forced to stop. ADA University with 161 employees is striving to be the prestigious educational institution not just in Azerbaijan, but also in the region. Offering education in English language, supportive student life, international staff and students, diversity, cooperation with high ranked universities outside Azerbaijan, career services, and other services make this university unique. All of these services to be in high quality demands hard work in the back by the staff members. Thus, performance appraisal is always needed not to just appraise them for their results, but also to maintain that motivation of employees, train them for their development, align their performance to some rewards. Nonetheless, the PA system stopped and employees could not be evaluated against their tasks. In the literature review part the question of what performance management and an appraisal are widely explained. While trying to search for answers to the identified research questions to reboot the PA system, surveys and interviews have been done with staff members and managers respectively. Here quantitative and qualitative approaches are used, 6 hypothesizes established and a regression analysis run. Based on the findings recommendations part was built with a table of action at the end.
Keywords: Business; ADA University -- Azerbaijan.; Staff training -- Azerbaijan.; Performance appraisal -- Azerbaijan.